Contracting matters: Hedging producers and consumers with a renewable energy pool - Karsten Neuhoff; Fernanda Ballesteros; Mats Kröger; Jörn C. Richstein (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Renewable energy installations are rapidly gaining market share due to falling technology costs and supportive policies. Meanwhile, the energy price crisis resulting from the Russian-Ukrainian war has shifted the energy policy debate toward the question of how consumers can benefit more from the low and stable generation costs of renewable electricity. Here we suggest a Renewable Pool ('RE-Pool') under which the government passes the conditions of Contracts-for-Difference on to consumers who thereby benefit from reliably low-cost electricity supply. We assess the effect on financing costs, scale, and system friendliness of wind investments, as well risk hedging for consumers' volume risks and hedging incentives.
Keywords: D44; D47; G32; L94; 330; Contracts-for-Difference; Renewable Policy; Electricity markets; Financing; PPA